Discontinuities that arise when designing for educational improvement at state scale - Stephan, Michelle; McCulloch, Allison; Schwartz, Catherine; Wilson, Holt; Mawhinney, Katherine (Frontiers in Education, 2025)
This paper explores the tensions—or discontinuities—that arise when designing for educational improvement at scale through research-practice partnerships (RPPs). Focusing on a statewide mathematics education initiative, the authors examine the complexities of coordinating work across diverse communities of practice and analyze how identity, power, and meaning-making impact collaborative problem definition. Drawing on Wenger’s dualities of participation-reification and identification-negotiation, the study highlights three recurring discontinuities: navigating the ambiguity of the design process, designing for diverse system stakeholders, and negotiating shared vocabulary. Through qualitative analysis of team reflections, activities, and artifacts, the paper offers practical strategies—such as participation structures and system mapping—to support productive boundary encounters and restore continuity. These insights advance both theory and practice for those undertaking equity-oriented design at large scale.